Education Innovation: Collaboration between the Merdeka Curriculum and the Madrasah Diniyah-based Curriculum to Form Holistic Students - Sari, Frisca Nur; Rif'ah, Maziyya Naila; Aminah, Siti Aminah (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The current learning process tends to focus more on cognitive aspects, such as mastery of theory, while the development of practical skills (psychomotor) and attitudes (affective) remains less optimal. Therefore, solutions are needed to address this issue. The purpose of this study is to describe educational innovation through the collaboration of the